Effect of kenaf fibre Mat layers and Zinc Oxide Nanoparticle Concentration on the Mechanical and Thermal Properties of ZnONPs/kenaf/polyester Composites. (December 2018) - Mohammed, Mohammed; Rahman, Rozyanty; Mohammed, Aeshah M.; Osman, Azlin F.; Adam, Tijjani; Dahham, Omar S.; Hashim, U.; Noriman, Nik Z.; Betar, Bashir O.
Abstract: Zinc oxide nanoparticle kenaf polyester composite (ZnONPs/kenaf/polyester) containing 1, 2, 3 and 4 layers of kenaf fibre treated with 40nm 2% (w/w) and 5 % (w/w ) of ZnONPs were prepared and characterised to evaluate the mechanical and thermal properties. The composites were prepared based on 4 kenaf layers and 2%, 5% (w/w) ZnONPs concentrations, all the samples were compared with control systems containing zero kenaf fibre and untreated with ZnONPs to save as references. The composites were fabricated using cold mixed blend via compression sandwich mould technique. The composites with 1 layer 5% (w/w) ZnONPs treated had the lower tensile strength and lower modulus suggesting it higher flexibility compared with those systems containing high number of layers, similar trend were seen in 2% (w/w) treated ZnONPs concentrations. The mechanical properties of composites containing 5% (w/w) ZnONPs demonstrated that the addition of fibre layers to the ZnONPs[kenaf/polyester was affected more than the 2% (w/w). While thermogravimetric analysis of 5% (w/w) and 2% kenaf composites incorporated with 1 and 4 layers were equally compared. The (5%) ZnONPs/kenaf/polyester treated revealed no significant changes in the decomposition temperature and showed no thermal transitions, this suggesting that it is non-biodegradable. Both results of the mechanical and thermal properties test suggest that the 1% (w/w) provide the based mechanical and thermal stable composite with novel biodegradability.